Daytime sleepiness and sleep quality in school performance of adolescents from a state educational institution - Cruz Aquino, Lincol Marx (2022)
Objective. To determine the association between daytime sleepiness and sleep quality with school performance in adolescents of the Institution Educative “Emblemática” Ventura Ccalamaqui, Barranca, 2018. Methods: Non-experimental and cross-sectional study. The sample included 217 adolescents of third and fourth year of secondary school. The Epworth Sleepiness Scale and the Pittsburgh Sleep Quality Index were applied. School performance was determined by the grade in communication and mathematics (subjects used by the international community) and was classified according to the National Curriculum (AD, A, B, C). Results. The average age of the adolescents was 15.9 ± 0.6 years, where 51.2% were female, 51.6% consumed coffee, tea and / or soft drinks less than once a week. It was observed that 49.7% suffered from daytime sleepiness, 84.8% had sleep problems and 52.1% presented an expected performance. Daytime sleepiness was significantly associated with school performance (p=0.004); students with daytime sleepiness presented expected and in-process school performance, students without daytime sleepiness presented outstanding, expected and ongoing school performance. The quality of sleep of adolescents was significantly associated with their school performance (p=0.045) and daytime sleepiness (p=0.015). Conclusions: Daytime sleepiness and sleep quality were associated with school performance, in adolescents of the Institution Educative “Emblemática” Ventura Ccalamaqui, Barranca, 2018.